Identitas dan Representasi: Karakter Lothar dan Lobo dalam Komik Amerika (Lingua, 2019)
The superhero genre comics can be inspirational and demonstrate moral codes that benefit society. To ignore some of the problematic aspects of identity of the genre would prevent necessary correctives from taking place. While the portrait of female, minority, and homosexual characters has improved through time in terms of representation and nonstereotypical characterizations, the default superhero remains a white character. Minority characters that appeared in the earlier eras of American comic books were much more likely to be villains than heroes. The research describes and anaylizes the racial representations and cultural destruction of colored superheroes named Lothar and Lobo from the earliest American comics. The research argues that representations provide a template for how colored superheroes are actively disvalued and controlled regardless of their collective memory authentic to their historically complex experience. Finally, it suggests that Lothar and Lobo are rhetorically racialized to better fit with with the basic premise of supremacy concepts.